Research on Environmental Adaptability of Advanced Reinforcement Structure in Marine Environment - ZHAO Lian - hong, ZHANG Hong - fei, LIU Yuan - hai, LIU Cheng - chen, WANG Hao - wei (Cailiao Baohu)
For carrying out the environmental adaptability research of advanced reinforcement structure in marine environment, the corrosion resistance of advanced reinforced structure in marine environments were studied through accelerated corrosion tests in the laboratory. In addition, the experiments included 5 cycles of corrosion environment test and crack growth test. Results showed that the advanced reinforcement structure had not corroded after 5 cycles of corrosion environment test, indicating that the corrosion protection performance of advanced reinforcement structure in the marine environment could meet the requirements, and also indicating that advanced reinforcement structure could decrease effectively reduce the crack growth rate. In conclude, the protection system of advanced reinforcement structure in marine environment meets the requirements of corrosion protection and can effectively improve the performance of damage tolerance performance.